How did Wolfgang Amadeus Mozart adjust his compositional technique when writing for a Mezzosoprano en travesti? A comparison between the roles of Cherubino and Sesto - Pretorious, Ane Sophia (College of Music, 2019)
Heroic male operatic roles were not always limited to what is today mainly known as male voices (tenor or baritone/bass). In the seventeenth and eighteenth centuries prepubescent boys were often castrated in order to keep their voices within the treble range. Some of these boys were extremely musical and after many years of vigorous training, went on to become renowned singers. The singing castrati were famous for their ethereal vocal abilities as well as ‘angelic’ vocal timbre. During the castrati’s reign, Wolfgang Amadeus Mozart wrote what is speculated to be the first operatic prepubescent boy role to be sung by a female en travesti, which set in motion a new opera tradition. Between 1790 and 1825 the convention of castration purely for the sake of voice preservation began to lose strength until the complete demise of these celebrated singers in 1922. From then on theatres began to substitute female singers, falsettists and countertenors into these heroic male roles. The repertoire of mezzo-sopranos today consists mainly of these prepubescent boy and adult heroic male roles. Based on the various physiological differences between the castrato and female body and larynx, this study focused mainly on proving how Mozart wrote idiomatically differently for the castrato and the female voice. The secondary aim was to determine the influence of socio-political climate on the perception of these roles by past and present audiences, as well as to uncover the various difficulties facing contemporary mezzosopranos. Recommendations aimed at mezzo-sopranos were formed from a mezzo-soprano’s perspective